Impact of Climate Change on Fishes in Complex Antarctic Ecosystems - Mintenbeck, Katja (2012)
Antarctic marine ecosystems are increasingly threatened by climate change and are considered to be particularly sensitive because of the adaptation of most organisms to cold and stable environmental conditions. Fishes play a central role in the Antarctic marine food web and might be affected by climate change in different ways: (i) directly by increasing water temperatures, decreasing seawater salinity and/or increasing concentrations of CO2; (ii) indirectly by alterations in the food web, in particular by changes in prey composition, and (iii) by alterations and loss of habitat due to sea ice retreat and increased ice scouring on the sea floor. Based on new data and data collected from the literature, we analyzed the vulnerability of the fish community to these threats.The potential vulnerability and acting mechanisms differ among species, developmental stages and habitats. The icefishes (family Channichthyidae) are one group that are especially vulnerable to a changing South Polar Sea, as are the pelagic shoal fish species Pleuragramma antarcticum. Both will almost certainly be negatively affected by abiotic alterations and changes in food web structure associated with climate change, the latter additionally by habitat loss. The major bottleneck for the persistence of the majority of populations appears to be the survival of early developmental stages, which are apparently highly sensitive to many types of alterations. In the long term, if climate projections are realized, species loss seems inevitable: within the demersal fish community, the loss or decline of one species might be compensated by others, whereas the pelagic fish community in contrast is extremely poor in species and dominated by P. antarcticum. The loss of this key species could therefore have especially severe consequences for food web structure and the functioning of the entire ecosystem.